2016
DOI: 10.1111/jfpp.12863
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Total Phenolic Compounds in Common Beverages Using CdTe Quantum Dots

Abstract: In this study, we describe a method of total phenolic compounds determination based on CdTe quantum dot (QD) fluorescence recovery in the presence of analyte. Polyphenols present in the solution were reducing agents, acting as electron donors to the CdTe–sodium periodate system, thus leading to perturbation of the transfer of excited electrons from QD to the acceptor molecules occurring in the absence of polyphenols. Using the developed technique the polyphenol content in green tea, black tea, Pu‐Erh tea, lemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…When tested vs. different antioxidant molecules, intensity of the color response was observed in this order: catechin, gallic acid > caffeic acid > ascorbic acid > coumaric acid > vanillic acid > ferulic acid > cinnamic acid. This is in agreement with the antioxidant polyphenols classical reactivity (i.e., flavonoids > o -phenol > m -phenols) [ 41 , 43 , 60 ]. Antioxidant activity of tea and wine samples was assessed expressing the data as gallic acid equivalents and using visual inspection by a digital camera.…”
Section: Optical Sensingsupporting
confidence: 84%
See 1 more Smart Citation
“…When tested vs. different antioxidant molecules, intensity of the color response was observed in this order: catechin, gallic acid > caffeic acid > ascorbic acid > coumaric acid > vanillic acid > ferulic acid > cinnamic acid. This is in agreement with the antioxidant polyphenols classical reactivity (i.e., flavonoids > o -phenol > m -phenols) [ 41 , 43 , 60 ]. Antioxidant activity of tea and wine samples was assessed expressing the data as gallic acid equivalents and using visual inspection by a digital camera.…”
Section: Optical Sensingsupporting
confidence: 84%
“…No comparison with existing methods was reported. CdTe QDs fluorescence recovery in the presence of the analyte was proposed by Dwiecki et al [ 60 ]. Polyphenols acted as electron donors for the CdTe–sodium periodate system, leading to perturbation of the transfer of excited electrons from QD to the acceptor molecules occurring in the absence of polyphenols.…”
Section: Optical Sensingmentioning
confidence: 99%
“…In biological applications, QDs as well as fluorophores have become important [ 66 ], because of the possibility to size-tune fluorescent emissions as a consequence of the core size, shape and material [ 22 ]. Dwiecki et al, suggested an approach for total phenolic compounds identification of common drinks (tea and coffee) based on CdTe QDs fluorescence in the presence of an analyte [ 67 ]. Polyphenols acted as reducing agents with the ability to transfer electrons to the CdTe-sodium periodate system leading to perturbation of the conduction of excited electrons from QD to the acceptor molecules happening in the absence of polyphenols.…”
Section: Optical Sensors and Assaysmentioning
confidence: 99%
“…Recent interest in utilizing metal nanoparticle (NP) assays for determination of TAC in food and plant extract samples has been growing . Many of these NP assays have been validated against other methods, including the Folin–Ciocalteu assay or CUPRAC assay and one gold nanoparticle assay has been validated with quantitative HPLC measurements . Özyürek et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in utilizing metal nanoparticle (NP) assays for determination of TAC in food and plant extract samples has been growing (16)(17)(18)(19)(20)(21). Many of these NP assays have been validated against other methods, including the Folin-Ciocalteu assay (19) or CUPRAC assay (17,18) and one gold nanoparticle assay has been validated with quantitative HPLC measurements (21). Özyürek et al (17) provided an excellent report of a developed and validated silver nanoparticle antioxidant capacity (SNPAC) assay for the measurement of the antioxidant capacity of polyphenols.…”
Section: Introductionmentioning
confidence: 99%